Effective Methods Of Conducting Inclusive Educational Process With Grades 1–2 - Tashboyeva, Mohinur (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines effective methods of implementing inclusive education in primary school, particularly in grades 1–2. The study analyzes key pedagogical approaches such as individualization, differentiated instruction, interactive teaching methods, and group-based learning. It also highlights the importance of creating an inclusive learning environment, enhancing teachers’ professional competence, and fostering collaboration with parents. The findings indicate that the proper application of inclusive teaching strategies positively influences students’ academic performance and social adaptation. The research emphasizes that inclusive education plays a crucial role in ensuring equal learning opportunities for all children in the early stages of schooling.